Environmental education and digital solutions: An analysis of the Lebanese context’s existing and possible digital actions - Khalifé, Mona; Chaker, Rawad; Gasparovic, Slaven (Frontiers in Education, 2022)
One of the main purposes of environmental education is to tackle the youths believes system and raise specific concerns linked to ecology and sustainability. Nonetheless, the educational approach of the ecological topics concerns is partly about the used means to reach effective results. The advancement of technologies and the rapid widespread of social media accelerated the use of online means of communication. While technology and digital tools have been proven to be effective for educational purposes, it becomes necessary to examine the relation between technology and environmental education, particularly in the Lebanese context. This position paper provides a review of studies about education, environment and digital tools, and more specifically studies conducted in Lebanon. We particularly focus on the educational institutions’ engagement and the social incentives to raise environmental awareness and develop ecological behaviors in Lebanon. The results of this study will help stakeholders and researchers for future implementation of digital solutions in the Lebanese context towards a green agenda.